Model Dukungan Sosial Berbasis Health Belief Model untuk Meningkatkan Penerimaan Diri terhadap Stigma dan Diskriminasi Pasien TB - Mau Leon, Fransiska Fabiola; Sukartini, Tintin; Makhfudli, Makhfudli; Luwarsih, Hesti Warastuti (Journal of Telenursing (JOTING), 2024)
This study aims to develop an effective intervention to improve self-acceptance of TB patients who experience stigma and discrimination using the Health Belief Model-Based Social Support approach. Web of Science, ProQuest and Pubmed databases were used to search for keywords derived from the Medical Subject Headings (MeSH) system for relevant articles in the preparation of this systematic. The results showed the initial literature search yielded 74 articles (48 Web Of Science, 7 from Proquest and 19 from Pubmed). After reviewing the abstracts for relevance and matching the inclusion criteria, 21 articles were selected for full-text review. Finally, 16 articles were selected for review and the results of the 16 articles analyzed showed that social support with the Health Belief Model can help reduce stigma and discrimination in TB patients. The conclusion of this study is that the results of the systematic review provide evidence for policy makers to consider alternative interventions using this method to fight stigma and discrimination so that the treatment process of TB patients becomes faster. Keywords: Social support Models, Health belief Model, Accept Yourself, Tuberculosis, Stigma, Discrimination.